Profil Fitokimia dan Aktivitas Antibakteri dari Massoia aromatic Becc., Acorus calamus L., dan Allium sativum L. terhadap Bakteri Penyebab Rinosinusitis - I Made Sugata; I Kadek Darmo Suputra; Putu Emy Suryanti; Made G. Juniartha; I Gusti Agung Ayu Kartika (Jurnal Ilmiah Medicamento, 2023)
Triketuka, an herb with multiple therapeutic activities, is featured in Balinese medicinal texts. This herb is composed of Massoia aromatic Becc. (masoyi), Acorus calamus L. (dringo), and Allium sativum L. (garlic). The antibacterial activity of these ingredients against bacteria causing rhinosinusitis has not been fully evaluated. Hence, this study seeks to determine the potential of these three components, especially with regards to their effectiveness against rhinosinusitis. In this research, an in vitro antibacterial test was conducted against Streptococcus aureus, Staphylococcus epidermidis, Escherichia coli, and Pseudomonas aeruginosa. The phytochemical profile of each plant was determined using Liquid Chromatography-Mass Spectrometry. The Minimum Inhibitory Concentration value was determined by carrying out the antibacterial test via the microdilution method. The detected compounds were analyzed for their contributions through the prediction of activity spectra for biologically active substances (PASS) online and Antibac-Pred. As a result of the in vitro antibacterial test, the samples were found to have MIC > 4096 ppm against all bacteria except Massoia aromatic and Acorus calamus against Staphylococcus aureus in MIC 4096 ppm each. This discovery was further verified through PASS online and Antibac-Pred. The studies indicate that certain compounds found in the samples exhibit antibacterial activity, albeit with low efficacy against the tested bacteria. In conclusion, the plants exhibit low antibacterial potential against bacteria that cause rhinosinusitis. Further research on the combination of the three plants is required to enhance their antibacterial efficiency.